Strategic orientation and performance of small medium enterprises: The moderating role of entrepreneurial networking - Asif, Muhammad Uzair (2022)
The main objective of this research is to examine the moderating role of entrepreneurial networking on the relationship between strategic orientation and performance of small and medium enterprises in the leather sector. Strategic orientation in the current research is composed of entrepreneurial orientation, market orientation, and learning orientation. Due to declining growth rate of leather sector small and medium enterprises, the data has been collected from small and medium enterprises operating in the leather sector Sialkot and Karachi Pakistan, using a cross-sectional study design. The study adopted systematic sampling and collected data from 374 respondents using questionnaires. The data was collected using the personally administered method and other social media like WhatsApp, Email, SMS, etc. In order to analyze the proposed framework and hypothesis, Partial Least Squares Structural Equation Modeling was used. The findings revealed a strong relationship between entrepreneurial orientation, market orientation, learning orientation, and performance of small and medium enterprises in the leather sector of Sialkot and Karachi Pakistan. Likewise, entrepreneurial networking has a significant moderating effect over the relationship between entrepreneurial orientation, market orientation, learning orientation, and the performance of small and medium enterprises. The findings strengthen the proposition of Resource Based View with the support of Resource Dependency Theory and identified that along with internal resources, outside resources that are achieved from entrepreneurial networks are compulsory for achieving success. The results of this study provide important insights to owners and managers, policymakers, and researchers to further understand the effects of entrepreneurial orientation, market orientation, learning orientation over the performance. Lastly, limitations of the current study and avenues for further research are discussed.